Hiệu chỉnh giá trị độ sâu, Magnitude của các trận động đất điều tra trong nhân dân (1903-1962) - Sơn, Lê Tử; Cẩm, Nguyễn Thị (Vietnam Journal of Earth Sciences, 2002)
Re-evaluation of the depth and the magnitude of earthquakes detected by macroseismic inversti gations (1903-1962)